Clinical Evaluation of the Safety, Efficacy and Tolerability of Lanthanum Carbonate in the Management of Hyperphosphatemia in Patients with End-Stage Renal Disease - Cernaro V (Therapeutics and Clinical Risk Management, 2020)
Valeria Cernaro, Sebastiano Calimeri, Alfredo Laudani, Domenico Santoro Unit of Nephrology and Dialysis, Department of Clinical and Experimental Medicine, University of Messina, Messina, ItalyCorrespondence: Valeria CernaroUnit of Nephrology and Dialysis, Department of Clinical and Experimental Medicine, University of Messina, Via Consolare Valeria N. 1, Messina 98124, ItalyTel/Fax +39.090.2212317Email valecern82@virgilio.itAbstract: Patients with progressive chronic kidney disease (CKD) commonly develop mineral and bone abnormalities and extraskeletal calcifications with following increased cardiovascular risk. A key pathophysiological role is played by hyperphosphatemia. Since diet and dialysis are often insufficient to control serum phosphorus levels, many patients require treatment with phosphate binders. Among them is lanthanum carbonate, an aluminum-free non-calcium-based compound. The present review summarizes the most recent literature data concerning the safety, efficacy and tolerability of lanthanum carbonate in patients with end-stage renal disease and hyperphosphatemia. The drug is taken orally as chewable tablets or powder with only minimal gastrointestinal absorption and resulting reduced risk of tissue deposition and systemic drug interactions. The dissociation of the drug in the acid environment of the upper gastrointestinal tract induces the release of lanthanum ions, which bind to dietary phosphate forming insoluble complexes then excreted in the feces. Even though there is no clear evidence that lowering serum phosphorus levels can improve patient-centered outcomes, a mortality beneﬁt with all phosphate binders, especially non-calcium containing ones, is not excluded. Lanthanum carbonate has been suggested to decrease all-cause mortality but not cardiovascular event rate compared to other phosphate binders. It induces a lower suppression of bone turnover than calcium carbonate and calcium acetate and may improve systolic function and cardiac dimension compared to calcium carbonate. Moreover, the use of lanthanum carbonate has been associated with better nutritional status compared to other phosphate binders, lower risk for hypercalcemia than calcium-containing binders, and amelioration of mild metabolic acidosis contrary to sevelamer hydrochloride. Main adverse effects include nausea, alkaline gastric reflux, gastric deposition of lanthanum, gastrointestinal obstruction, subileus, ileus, perforation, fecal impaction, and reduction of gastrointestinal absorption of some drugs including statins, angiotensin-converting enzyme inhibitors and some antibiotics such as fluoroquinolones or tetracyclines.Keywords: adverse effects, chronic kidney disease-mineral bone disorder, CKD-MBD, hyperphosphatemia, lanthanum carbonate, phosphate binders